Tuberculous Spondylitis involving Sacrum- a rare location and presentation of Pott’s disease: Case report and review of the Literature - Khan, Shahidul Islam; Ahmed, Nazmin; Rahman, Asifur; Mahmud, Abdullah Al; Islam, Rafiqul; Ahsan, Md Kamrul (Bangladesh Journal of Medical Science, 2019)
Background: Spinal tuberculosis is a common form of extrapulmonary manifestation of tuberculosis. Among them tubercular involvement of the lumbosacral region or isolated involvement of sacram is very rare presentation. Aim of the work: The aim of this case presentation is to describe two rare cases of Pott’s disease which clinically mimicked spinal tumor. Case report: A 60-year-old hypertensive, diabetic male patient admitted with low back pain radiating to both lower limbs for 7 months along with low grade fever, generalized weakness and weight loss for the same duration. Clinically, patient had features of flaccid paraparesis, tenderness at the lumbosacral junction, restricted SLR on both sides. There was no features of autonomic dysfunction. MRI of lumbosacral spine showed infective spondylodiscitis at L4 to S1 level with collapse of L5 vertebrae along with paravertebral and epidural abscess. Diagnosis was confirmed by CT guided FNAC from the lesion. Next case was a 23-year-old male patient presented with back pain and walking difficulty for 5 months with some constitutional symptoms.MRI of the dorsal spine with whole spine screening showed multifocal skipped lesion involving whole spine with presence of huge presacral collection. Percutaneous transpedicular aspiration of the purulent material under C-Arm guidance was done and tuberculous infection confirmed by Gene Xpert. Conclusion: Though sacral tuberculosis is rare presentation of Pott’s disease but it should be considered as one of the differential diagnosis in any lytic lesion involving the sacrum in perspective of our country. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.440-445